MALARIA AND DEATH OF WOMEN OF CHILD- BEARING AGE IN KASSALA - Mohammed, Abdalla Ali; Abdelfattah, Ahmed Ibrahiem; Elnour, Mahgoub Hassan (Gezira Journal of Health Sciences, 2006)
A retrospective, community-based survey of reproductive age mortality in refugees, acute internally displaced people, slum dwellers and urban population in Kassala Province  Eastern Sudan. Slum dweller sector shows the highest reproductive age mortality rate 314/100,000 WRA, while urban sector shows the lowest rate 199/100,000 WRA. Maternal mortality rate is highest in IDP population and slum dwellers (168 & 126/100,000 WRA respectively) and lowest in urban population 47/100,000 WRA). Maternal mortality ratio is very high in slum dweller, IDP & refugee population (1,207, 1,192 and 914/100,000 live births respectively), and 367 per 100,000 live births in urban population. Malaria is the major cause of death in three sectors with exception of IDP where pregnancy related causes contribute to 70% of the deaths. This study shows the big toll of malaria on the health of females in child bearing age, the high discrepancy in reproductive age mortality and maternal mortality between different population sectors in the same location. It also discusses the causes of these deaths.